STUDIES ON THE MECHANISM OF ACTION OF IONIZING RADIATIONS : II. INHIBITION OF SULFHYDRYL ENZYMES BY ALPHA, BETA, AND GAMMA RAYS - Barron, E. S. Guzman (The Rockefeller University Press, 1949)
The activity of crystalline phosphoglyceraldehyde dehydrogenase and urease was decreased when dilute solutions of these sulfhydryl enzymes were irradiated with small doses of alpha rays from Po, beta rays from Si(89), and gamma rays from Ra. Partial reactivation of the enzyme by addition of glutathione was obtained after inhibition with alpha rays. Evidence that these inhibitions are due to oxidation of the —SH groups of the enzymes was given by the irradiation of the mercury-mercaptide urease with gamma rays. This irradiated complex was completely reactivated by glutathione as was the non-irradiated enzyme. The ionic efficiency of all these ionizing radiations on inhibition of phosphoglyceraldehyde dehydrogenase was similar (ionic yield around 1). The sulfhydryl groups of crystalline phosphoglyceraldehyde dehydrogenase were titrated by enzyme activity measurements and by ferricyanide oxidation.